Finite element modeling of reduced grain boundaries elasticity in nanocrystalline metals - Talakesh, Alireza; Torabi, Amir (Computational Continuum Mechanics, 2025)
Nanocrystalline metals consist of two distinct phases: the crystalline phase, namely grains, and the intercrystalline phase, which includes grain boundaries, triple junctions, and quadruple nodes. Weakening of elasticity in the intercrystalline phase of nanocrystalline metals, especially in grain boundaries, causes a decrease in the overall elastic modulus. Consequently, studying the elastic behavior and calculating the elasticity of grain boundaries are critical to the understanding of nanocrystalline metals. The purpose of this research is to model the elasticity of grain boundaries in nanocrystalline metals and calculate it. For this purpose, five different metal samples with different crystalline structures are considered. For each sample, three representative volume elements (RVEs) with different grain sizes and constant grain boundary thickness are modeled. The behavior of the crystalline phase is assumed to be elastic with cubic symmetry, while the behavior of grain boundaries is assumed to be elastically isotropic. Uniaxial tension is then simulated using a finite element analysis to calculate the Young’s modulus of the RVEs. The weakening coefficient for grain boundaries is obtained through this analysis. To verify the validity of this coefficient, the Young’s modulus of the simulated RVEs is compared with the Young’s modulus extracted from molecular dynamics simulation and experiments reported in the literature.